2014
DOI: 10.1016/j.yebeh.2014.09.061
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of once-daily extended-release topiramate (USL255): A subgroup analysis based on the level of treatment resistance

Abstract: Results from a previously conducted global phase III study (PREVAIL; NCT01142193) demonstrate the safety and efficacy of once-daily USL255, Qudexy™ XR (topiramate) extended-release capsules, as adjunctive treatment of drug-resistant partial-onset seizures (POSs). In this study, we report a post hoc analysis of PREVAIL data according to patient level of treatment resistance (based upon the number of concomitant antiepileptic drugs [AEDs] and lifetime AEDs) at baseline, with patients defined as either having "hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…2 This definition strongly relied on a study of a large cohort of patients from Glasgow, Scotland, which showed that after failure of 2 monotherapy AEDs, the chance of the use of a third drug to produce seizure freedom was <10%. 8 However, other studies show that patients respond favorably to >2 AED trials, 9,10 so the current study gives further evidence that persistence in treatment with AEDs, typically working with at least 4 AEDs over approximately 3 years, will yield positive results for patients.…”
Section: Commentarymentioning
confidence: 54%
“…2 This definition strongly relied on a study of a large cohort of patients from Glasgow, Scotland, which showed that after failure of 2 monotherapy AEDs, the chance of the use of a third drug to produce seizure freedom was <10%. 8 However, other studies show that patients respond favorably to >2 AED trials, 9,10 so the current study gives further evidence that persistence in treatment with AEDs, typically working with at least 4 AEDs over approximately 3 years, will yield positive results for patients.…”
Section: Commentarymentioning
confidence: 54%
“…In regard to the post hoc analysis of efficacy by drug refractoriness, the authors acknowledge that the International League Against Epilepsy (ILAE) definition of drug-resistant epilepsy ("failure of adequate trials of two tolerated and appropriately chosen and used AED schedules") [27] was not used, as the PREVAIL OLE study design prevents verification of patient participation in two "adequate trials". Therefore, the definition for drug resistance in the post hoc analyses was based on clinical experience and a pharmacoeconomic study that classified 'patients with refractory seizures' as those on three or more AEDs [12,28]. Despite the limitations of defining drug resistance, many patients responded favorably to addition of USL255.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were also evaluated for seizure-free intervals (defined as the percentage of patients who were seizure-free for an interval of 4, 12, 24, 36, or 48 weeks at any time during the study). Based on a surrogate measure of drug refractoriness (the number of current and lifetime AEDs), patients were divided into two groups: patients with ≥2 concurrent AEDs and ≥4 lifetime AEDs were defined as having "highly" drug-resistant seizures, while the rest of the study population comprised the group of patients with "less" drugresistant seizures (one concurrent AED and/or b 4 lifetime AEDs) [12].…”
Section: Assessmentsmentioning
confidence: 99%
“…На рис. 2 зображено ефективність застосування ад'ювантної терапії топіраматом у пацієнтів із фармакорезистентною епілепсією [21].…”
Section: механізм-індукований підхід до лікування пароксизмальних станівunclassified